Leviathan - Hobbes, Thomas, 1588-1679; Tuck, Richard, 1949- (Cambridge : Cambridge University Press, 1996)
Thomas Hobbes' Leviathan is arguably the greatest piece of political philosophy written in the English language. Written in a time of great political turmoil (Hobbes' life spanned the reign of Charles I, the Civil Wars, the Commonwealth and the Protectorate, and the Restoration), Leviathan is an argument for obedience to authority grounded in an analysis of human nature. Since its first publication in 1991 Richard Tuck's edition of Leviathan has been recognised as the single most accurate and authoritative text, and for this revised edition Professor Tuck has provided a much amplified and expanded introduction, which will provide students unfamiliar with Hobbes with a cogent and accessible introduction to this most challenging of texts. Other vital aids to study include an extensive guide to further reading, a note on textual matters, a chronology of important events and brief biographies of important persons mentioned in Hobbes' text.
Title from publisher's bibliographic system (viewed on 13 May 2019).
Keywords: elektronické knihy; electronic books; Political science -- Early works to 1800.; State, The